Does maternal feeding restriction lead to childhood obesity in a prospective cohort study? - Rifas-Shiman, S L (2010)
BACKGROUND: Some studies show that greater parental control over children’s eating habits predicts later obesity, but it is unclear whether parents are reacting to infants who are already overweight. OBJECTIVE: To examine the longitudinal association between maternal feeding restriction at age 1 and body mass index (BMI) at age 3 and the extent to which the association is explained by weight for length (WFL) at age 1. METHODS: We studied 837 mother–infant pairs from a prospective cohort study. The main exposure was maternal feeding restriction at age 1, defined as agreeing or strongly agreeing with the following question: “I have to be careful not to feed my child too much.” We ran multivariable linear regression models before and after adjusting for WFL at age 1. All models were adjusted for parental and child sociodemographic characteristics. RESULTS: 100 (12.0%) mothers reported feeding restriction at age 1. Mean (SD) WFL z-score at age 1 was 0.32 (1.01), and BMI z-score at age 3 was 0.43 (1.01). Maternal feeding restriction at age 1 was associated with higher BMI z-score at age 3 before (β 0.26 (95% CI 0.05 to 0.48)) but not after (β 0.00 (95% CI −0.17 to 0.18)) adjusting for WFL z-score at age 1. Each unit of WFL z-score at age 1 was associated with an increment of 0.57 BMI z-score units at age 3 (95% CI 0.51 to 0.62). CONCLUSIONS: We found that maternal feeding restriction was associated with children having a higher BMI at age 3 before, but not after, adjusting for WFL at age 1. One potential reason may be that parents restrict the food intake of infants who are already overweight.